The Nexus between Energy Consumption and Financial Development with Asymmetric Causality Test: New Evidence from Newly Industrialized Countries - Zeren, Feyyaz; Koc, Mustafa (International Journal of Energy Economics and Policy, 2013)
In this study, the relationship between energy consumption and financial development is investigated via Hatemi-J asymmetric causality test (2012) which is able to separate positive and negative shocks in analysis. In order to determine different dimensions of financial system, deposit money bank assets to GDP (dbagdp), financial system deposits to GDP (fdgdp) and private credit to GDP (pcrdbgdp) were used as three different indicators. As a result of this study on Newly Industrialized 7 Countries spanning the period 1971 till 2010, both positive and negative shocks existed for Malaysia and Mexico, causality from energy consumption to financial developments emerged for Philippines in only negative shocks. While two-way causality occurred for India, Turkey and Thailand, there was not for South Africa. Keywords: energy consumption; financial development; newly industrialized countries; asymmetric causality JEL Classifications: C32; O13; Q43